1993
DOI: 10.1093/hmg/2.11.1941
|View full text |Cite|
|
Sign up to set email alerts
|

The gene for Darier's disease maps to chromosome 12q23–q24.1

Abstract: Darier's disease is a rare autosomal dominant skin disorder in which there is abnormal adhesion between keratinocytes. It appears to be associated with an increased prevalence of neuropsychiatric disorders including mental retardation and epilepsy. In addition we have previously reported a family in which major affective disorder cosegregates with Darier's disease. In the present study we have localized the gene for Darier's disease to chromosome 12q23-q24.1 by linkage analysis in five British pedigrees. We ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0
3

Year Published

1997
1997
2007
2007

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 0 publications
5
67
0
3
Order By: Relevance
“…The autosomal dominant inheritable trait of DD was not identified until 1993, when the gene associated with DD was mapped to chromosome 12q23-24.1 by linkage analysis [13,14]. Later, in 1999, a group led by Alain Hovnanian and colleagues identified the ATP2A2 gene, which encodes the type 2 sarco(endo)-plasmic reticulum Ca 2+ -ATPase (SERCA2), as the causative gene for DD [12].…”
Section: Genetics Perspectivementioning
confidence: 99%
“…The autosomal dominant inheritable trait of DD was not identified until 1993, when the gene associated with DD was mapped to chromosome 12q23-24.1 by linkage analysis [13,14]. Later, in 1999, a group led by Alain Hovnanian and colleagues identified the ATP2A2 gene, which encodes the type 2 sarco(endo)-plasmic reticulum Ca 2+ -ATPase (SERCA2), as the causative gene for DD [12].…”
Section: Genetics Perspectivementioning
confidence: 99%
“…5,6 To date no genes demonstrating an unequivocal influence on susceptibility to BAD have been identified, although several chromosomal regions have been repeatedly implicated by different linkage studies (reviewed by Craddock and Jones 4 ). These include 4p, [7][8][9][10][11] 4q, 12,13 12q, [14][15][16][17] and 18p+q. [18][19][20][21][22][23][24][25][26] The fact that support for even the most promising loci is not universal is, of course, to be expected for a complex disorder in which the susceptibility genes exert modest individual effect sizes and interact with both other genes and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…14 In 1994, Craddock et al identified a pedigree cosegregating for bipolar disorder and Darier's disease, raising the possibility that the 12q23-q24 region encoded a potential bipolar disorder susceptibility locus. 6,15 While not confirmed in genome screens of pedigree cohorts, 16,17 studies of a very large French Canadian pedigree 18 and two Danish pedigrees 19 have provided significant evidence for linkage to this region.…”
Section: Introductionmentioning
confidence: 99%